Trends in oxygenate/hydrocarbon selectivity for electrochemical CO(2) reduction to C2 products - Peng, Hong-Jie; Tang, Michael T.; Halldin Stenlid, Joakim; Liu, Xinyan; Abild-Pedersen, Frank (Nature communications, 2022)
The electrochemical conversion of carbon di-/monoxide into commodity chemicals paves a way towards a sustainable society but it also presents one of the great challenges in catalysis. Herein, we present the trends in selectivity towards specific dicarbon oxygenate/hydrocarbon products from carbon monoxide reduction on transition metal catalysts, with special focus on copper. We unveil the distinctive role of electrolyte pH in tuning the dicarbon oxygenate/hydrocarbon selectivity. The understanding is based on density functional theory calculated energetics and microkinetic modeling. We identify the critical reaction steps determining selectivity and relate their transition state energies to two simple descriptors, the carbon and hydroxide binding strengths. The atomistic insight gained enables us to rationalize a number of experimental observations and provides avenues towards the design of selective electrocatalysts for liquid fuel production from carbon di-/monoxide. Key mechanistic steps for selective CO (2) reduction over Cu into hydrocarbon versus oxygenated C 2 products are identified by atomistic and microkinetic modeling. Variations in C and OH binding are found to predict catalytic selectivity of materials.